Improvement on efficiencies of dilute alkaline water electrolyzer using membranes. (28th December 2016) - Shau, Abhra; De, P.; Ray, P.
Abstract: Electrolysis of 0.50% (w/v) aqueous KOH solution with novel packed bed electrodes made of SS 316 solid cylindrical packing has been carried out using membranes with three different combinations, namely Poly vinyl alcohol-acrylamide (PVA-AAm), Poly vinyl alcohol-Acrylic acid (PVA-AAc) and Poly vinyl alcohol-Acrylic acid-acrylamide (PVA-AAc-AAm). For production of hydrogen, nearly 100% current efficiency and about 50% energy efficiency have been achieved by using PVA-AAc and PVA-AAc-AAm membranes. FTIR analyses of fresh and used membranes as well as AAS analyses of anolyte and catholyte confirm that membranes prevent transportation of Fe ions from anode to cathode resulting in better current and energy efficiencies for production of hydrogen and oxygen. PVA-AAm membrane has been found to be unsuitable as AAm reacts and decomposes to AAc during electrolysis in dilute KOH solution. The ratios of production rates of hydrogen to oxygen reach the steady state value of 2 in 2 h which confirms the consumption of oxygen by undesired reactions at initial stages. Highlights: Acid and amide membranes have been prepared with poly vinyl alcohol as base. Current efficiency ≈100% achieves using PVA-AAc and PVA-AAc-AAm membranes. Energy efficiency for H2 production ≈50% achieves using these membranes. Stability of membranes under electrolytic conditions has been analyzed using FTIR. Membranes disallowed migration of Fe ion(s) – confirms by FTIR and AAS analyses.